2015
DOI: 10.7547/14-002.1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinical study on 37 subtalar arthrodesis patients of nine years follow-up

Abstract: Subtalar arthrodesis is effective treatment for subtalar joint disease but could induce joint degeneration and ankle joint motion limitation related to talar declination and hindfoot height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1,5 However, several studies have suggested that subtalar joint fusion can lead to asymptomatic tarsal bone arthritis, degeneration, and limited joint motion. 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 However, several studies have suggested that subtalar joint fusion can lead to asymptomatic tarsal bone arthritis, degeneration, and limited joint motion. 6…”
Section: Introductionmentioning
confidence: 99%
“…1,5 However, several studies have suggested that subtalar joint fusion can lead to asymptomatic tarsal bone arthritis, degeneration, and limited joint motion. 6 Various types of incisions are currently used for subtalar joint arthrodesis, including lateral incisions such as an arc incision across the tarsal sinus, an oblique incision from the lateral malleolus point to the fourth metatarsal, and the traditional L-shaped incision. 5,7 Selection of the most appropriate incision is based on any previous surgeries, the soft tissue condition, and any internal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic measurements help to identify malalignment of the hindfoot that needs to be addressed at the time of surgery 5 . In addition to hindfoot malalignment, it is important to look for loss of calcaneal height and a change in the talar inclination 6 . A decreased talar declination angle causes anterior ankle impingement, which will ultimately result in ankle arthritis 7 .…”
Section: Introductionmentioning
confidence: 99%